1992
DOI: 10.1104/pp.99.4.1455
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Analysis of a Heat-Shock Response in Wheat

Abstract: We have isolated two cDNA clones from wheat (Triticum aestivum L. var Stephens), designated WHSP16.8 and WHSP16.9, that are highly similar in sequence to the low molecular weight heatshock protein genes previously isolated from soybean. RNA blot analysis confirms that these sequences are present in heat-shocked wheat seedlings, but not in control tissues. The WHSP16.8 and WHSP16.9 cDNAs were isolated by screening a lambda gt1l expression library with antibodies to HMGc (a chromosomal protein of wheat). Immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…HSP also appear during the course of normal plant development and tissue differentiation and may be induced by other environmental stresses, such as salt stress (McElwain and Spiker 1992;Kuznetsov et al 1993). Furthermore, under the complete absence of hyperthermia, HSP have been found in generative organs of clover flowers, seed pods and seeds; this leads to the speculation that besides their function in heat tolerance some HSP may play a role in the reproductive process (Hernandez and Vierling 1993).…”
Section: B) Synthesis Of Heat Shock Proteins I) Occurrence and Inductionmentioning
confidence: 99%
“…HSP also appear during the course of normal plant development and tissue differentiation and may be induced by other environmental stresses, such as salt stress (McElwain and Spiker 1992;Kuznetsov et al 1993). Furthermore, under the complete absence of hyperthermia, HSP have been found in generative organs of clover flowers, seed pods and seeds; this leads to the speculation that besides their function in heat tolerance some HSP may play a role in the reproductive process (Hernandez and Vierling 1993).…”
Section: B) Synthesis Of Heat Shock Proteins I) Occurrence and Inductionmentioning
confidence: 99%
“…4A). Another pair of cDNAs is HSP 16.9d [14] and 17LC1 (Genbank accession no. L37069) which are highly similar but HSP 16.9d will belong to the Tt2VC group and 17LCI belongs to TI2VT mRNA population due to a poly(A) site 20 bp downstream as compared to HSP 16.9d (Fig.…”
Section: Sequence Analysismentioning
confidence: 99%
“…Previously, we have isolated and characterized several members of these families in wheat including two members of HSP 16.9 family (for review see [ 15]). Two other members of HSP 16.9 family in wheat have been reported by McElwain and Spiker [ 13,14]. In vitro hybrid selection/translation and 2-D gel electrophoresis using the HSP16.9 cDNA probe indicated that this family consists of at least 12 members with differing pI values [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat‐shock proteins are a set of proteins whose synthesis is induced by heat stress (McElwain and Spiker 1992). The induction of heat‐shock protein synthesis in response to thermal stress occurs in all organisms, ranging from bacteria to humans (Vierling 1991).…”
Section: Introductionmentioning
confidence: 99%